Quantifying the Proteolytic Cleavage of Plasma Membrane Proteins in Living Cells. Issue 1 (7th August 2018) - Calamai, Martino; Pavone, Francesco Saverio
Abstract: The standard approach to study the activity of proteases consists of lysing cells and measuring the changes in the fluorescence properties of a synthetic substrate after cleavage in vitro. Here, a general protocol that uses a bi‐fluorescent chimeric construct of a known substrate protein that follows the proteolytic processing in living cells is described. This approach is useful, in particular, to search for pharmacological conditions altering the cleavage rate of a certain protease, or to investigate the biological factors influencing a certain proteolytic mechanism. Three different methods (microscopy, flow cytometry, and spectroscopy) to detect fluorescence changes due to alteration in the processing are described. This approach was originally developed for studying conditions affecting the proteolytic activity of the β‐secretase Bace1 on the amyloid precursor protein APP, but can in principle be applied to investigate any membrane protein undergoing ectodomain shedding by proteolytic cleavage. © 2018 by John Wiley & Sons, Inc.